PROTECTION OF DIGITAL PRIVACY RIGHTS AS A HUMAN RIGHT AGAINST PERSONAL DATA MISUSE IN INDONESIA - Faisal Fachri; Ariy Khaerudin; Nourma Dewi (Journal of International Islamic Law, Human Right and Public Policy, 2026)
The rapid development of information technology and internet usage has increased the risk of misuse of personal information in the digital space, in the form of data theft, dissemination, and utilization. This study aims to determine the form of protection of the right to privacy as a human right against misuse of personal data in Indonesia based on the Personal Data Protection Law. Using normative legal research with a legislative approach and a conceptual approach, the study results show that the Personal Data Protection Law has provided a legal basis for the rights of personal data subjects, the obligations of data controllers, and administrative and criminal sanctions for personal data violations. However, the implementation of the Personal Data Protection Law still faces various obstacles, such as low public awareness, weak supervision, and the persistently high number of personal data leaks. Therefore, it is necessary to strengthen supervision, law enforcement, and improve the digital literacy of the public to realize effective personal data protection in Indonesia.